Twin reversed arterial perfusion sequence: A case report. Issue 3 (22nd September 2020) - Yi, Jiao; Wu, Xiumei
Synopsis: The present study reports a case of twin reversed arterial perfusion syndrome with spontaneous interruption of blood supply in the acardiac twin.